A manufacturing cell formation problem with a maximum cell workload constraint. (14th October 2015) - Caramia, Massimiliano; Mari, Renato
Abstract : We address a manufacturing cell formation problem (CFP) in which one of the constraints limits the maximum cell workload to a given threshold. To meet such a requirement, it is possible to allocate copies of existing machines in different cells. Additional machines, however, increase costs and may also increase inter-cell flow. The proposed CFP is first modelled in terms of bilevel optimization and then reformulated as a single-level optimization problem. To the best of our knowledge, this is the first study addressing the CFP with a cell workload constraint as a bilevel optimization problem. The results of this paper have direct implications for real-world decision-making for at least two reasons. One is related to the methodology used that allows one to model the actual dynamic of the decision-making process more accurately. The second reason is that the proposed model enables better system efficiency when both machine and inter-cell material handling costs are minimized. Experimental results are presented and discussed.